HEP® (Homeostasis-Enrichment-Plasticity) Approach Changes Sensory-Motor Development Trajectory and Improves Parental Goals: A Single Subject Study of an Infant with Hemiparetic Cerebral Palsy and Twin Anemia Polycythemia Sequence (TAPS) - Aymen Balikci; Teresa A. May-Benson; Gamze Cagla Sirma; Gul Ilbay (MDPI AG, 2024)
Background: Early intervention (EI) for infants identified as being at high risk for cerebral palsy (CP), or who have been diagnosed with it, is critical for promotion of postnatal brain organization. The aim of this study was to explore the effectiveness of the Homeostasis-Enrichment-Plasticity (HEP) Approach, which is a contemporary EI model that applies the key principles of enriched environment paradigms and neuronal plasticity from experimental animal studies to ecological theories of human development on the motor development, sensory functions, and parental goals of an infant with twin anemia polycythemia sequence (TAPS) and CP. Methods: An AB phase with follow-up single case study design which consisted of multiple baseline assessments with the Peabody Developmental Motor Scales-2 (PDMS-2) and the Test of Sensory Functions in Infants (TSFI) was used. Non-overlapping confidence intervals analysis was used for pre-post PDMS-2 scores. The measurement of progress toward goals and objectives was conducted using the Goal Attainment Scale (GAS). The HEP Approach intervention consisted of 12 one-hour sessions implemented over a period of 3 months, where a physical therapist provided weekly clinic-based parental coaching. Results: Results found a stable baseline during Phase A and improvement in response to the HEP Approach intervention during Phase B in both the PDMS-2 and TSFI according to 2SD Band analysis. The confidence intervals for the PDMS-2 scores also indicated a significant improvement after HEP intervention. The scores for both the PDMS-2 and the TSFI were consistent or showed improvement throughout the Follow-Up phase. A GAS t-score of 77.14 indicated that the infant exceeded intervention goal expectations. Conclusions: Although our findings suggest that the HEP Approach intervention has promise in enhancing sensory functions, motor skill outcomes, and parental goals in an infant with TAPS and CP, further research is required to validate and apply these results more broadly.